Comparison of laparoscopic and open approach in the treatment of heterotopic pregnancy following embryo transfer - Chen, Shengfu; Zhu, Yingying; Xie, Meiqing (Frontiers in Surgery, 2022)
Abstract Purpose: Heterotopic pregnancy (HP) is a rare disease and lacks of standard treatment. Surgery is usually adopted by most doctors. The current research aimed to compare the perioperative and pregnancy outcome of two different surgical methods: laparoscopic approach and open surgery. Methods: Between October 2006 and December 2020, 101 suspected HP patients following embryo transfer were enrolled. After exclusion, 86 patients were used for further analysis. The demographic, perioperative and obstetric data were retrospectively analyzed. Results: Of these 86 patients, 62 underwent laparoscopic approach and 24 underwent open surgery. There was an increase in the adoption of laparoscopic approach over the years: 25% (6/24) patients in the 2006 – 2012 period compared with 90.3% (56/62) patients in the 2013 – 2020 period (p < 0.001). Compared with open surgery, patients treated by laparoscopic approach demonstrated lesser blood loss [20(10-50) vs. 30 (20-50) ml, p=0.036], and fewer days of hospital stay [5.0(4.0-7.3) vs. 9.5 (7-15.3) days, p<0.001]. During the laparoscopic procedure, no one needed to be converted to open surgery. However, the rates of first trimester miscarriage, preterm, cesarean section, birth weight and 1- and 5-min Apgar were similar (all p>0.05) between the two surgical methods. Conclusions: Comparing open surgery, laparoscopic approach showed comparable pregnancy outcomes but also a better performance on perioperative outcome than open surgery in the treatment of HP.